Dampak Dari Permainan Tradisional pada Perkembangan Motorik Kasar Anak Usia Dini Kelompok B di TK Kemala Bhayangkari 06 Tallo Kota Makassar - St. Adrianti (Lembaga Pengembangan Kinerja Dosen, 2025)
This quasi-experimental study aims to find out if playing traditional games like asingasing and dende can help young children in group B at TK Kemala Bhayangkari 06 Tallo improve their gross motor skills. We are testing the traditional games to see if they make a difference, and the main thing being studied is how well the children develop their gross motor skills. The study included all the children in group B, which had a total of 38 students. The sample was divided into two groups: group B1, which played the dende game and had 20 children, and group B2, which played the asingasing game and had 18 children. The researchers collected data using a checklist to observe the children. They also analyzed the data using descriptive and inferential methods. Result showed that playing traditional games like asingasing and dende helped children's gross motor development. The assessment showed that children who played the traditional games had average scores in the developing category, which was expected, and children who played the dende game even reached the very well-developed category.